Pedro Mejía Domínguez (1929 - 1996). Semblance - Andrade, Luis (1996)
He died in Lima, our dear friend, colleague and professor Dr. Pedro Mejía Domínguez. He was born in Lima in 1929. He completed his schooling at the Colegio La Salle. His innate vocation for study allowed early entry to our university, achieving complete his medical studies lso 24 years, when the race was done in nine.